(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The popular and frequently used Online Social Networks (OSNs) all have a conceptually centralized design, in which a single organization holds unprecedented amounts of personal information in terms of amount, variety, geographical expansion, or degree of detail. With no need for a question, this is one of the most serious dangers to customers’ privacy or right to secrecy. Since then, decentralization has been hailed as the solution for privacy concerns, particularly in the world of open source networks (OSNs). A more in-depth examination of the problem, however, indicates that, if not properly conceived and executed, decentralization may have much more negative impacts on users’ privacy than it may bring innovative answers. Furthermore, studies on Discrete Online Social Networks (DOSNs) have shown that there are additional hurdles to overcome to make them a reality, which necessitates additional attention and novel technological solutions. The difficulties of privacy preserving among centralization or decentralization are discussed in this study, as well as an overview of current research on decentralized private information social network services.